2019
DOI: 10.21815/jde.019.002
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education in U.S. Dental Hygiene Programs: Program Director Responses Before and After Introduction of CODA Standard 2–15

Abstract: A 2014 survey found that dental hygiene program directors perceived interprofessional education (IPE) as a priority for themselves and the dental hygiene profession in the U.S. The aim of this study was to explore whether IPE collaborations in dental hygiene programs and program directors’ attitudes changed from 2014 to 2017 since the Commission on Dental Accreditation (CODA) Standard 2–15 on IPE was introduced in August 2016. In May 2017, directors of all 325 U.S. dental hygiene programs were invited to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the light of specific periodontal treatment and dental hygiene process of care accreditation standards, integrating the new staging and grading system should not significantly change DH education programs. Since DH educational institutions must adhere to the accreditation standards, the extent to which these programs incorporate the new staging and grading system is driven by accreditation standards and guidelines 17,18 . Zorek and Furgeson studies concluded that the IPE was not integrated into DH programs because there was no explicit interprofessional education (IPE) mandate in the accreditation Standards 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of specific periodontal treatment and dental hygiene process of care accreditation standards, integrating the new staging and grading system should not significantly change DH education programs. Since DH educational institutions must adhere to the accreditation standards, the extent to which these programs incorporate the new staging and grading system is driven by accreditation standards and guidelines 17,18 . Zorek and Furgeson studies concluded that the IPE was not integrated into DH programs because there was no explicit interprofessional education (IPE) mandate in the accreditation Standards 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Since DH educational institutions must adhere to the accreditation standards, the extent to which these programs incorporate the new staging and grading system is driven by accreditation standards and guidelines 17,18 . Zorek and Furgeson studies concluded that the IPE was not integrated into DH programs because there was no explicit interprofessional education (IPE) mandate in the accreditation Standards 17,18 . These studies conjectured that if curricular content is explicitly stated in the accreditation standards, programs are almost certain to integrate it, whereas implicit verbiage in accreditation standards leaves it open to interpretation and, therefore, integration.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The number of interprofessional collaborations across schools has increased with the explicit inclusion of IPE in the Commission on Dental Accreditation (Standard 2-15) and Liaison Committee on Medical Education (Standard 19-A) standards. 19,20 In addition, the impact of accreditation on the health workforce can be observed in the temporal association between the addition of diversity standards and increased female, Black, and Hispanic matriculants in U.S. medical schools. 21 Similarly, the integration of public health standards by the Accreditation Council for Pharmacy Education (ACPE) incentivized pharmacy schools to align their curricula to meet these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…16–18 The number of interprofessional collaborations across schools has increased with the explicit inclusion of IPE in the Commission on Dental Accreditation (Standard 2-15) and Liaison Committee on Medical Education (Standard 19-A) standards. 19,20…”
mentioning
confidence: 99%
“…However, according to Furgeson and Inglehart's recent 2019 study, which surveyed 117 dental hygiene program directors across the United States, IPE was most likely to occur in volunteer extra‐curricular activities rather than through integrating mandatory IPE within curriculum 8 . Dental hygiene educators have been slow to incorporate IPE into their curricula, and only a few studies have assessed the effectiveness of IPE implementation in dental hygiene programs 9‐12 …”
Section: Introductionmentioning
confidence: 99%